2017
DOI: 10.1016/j.envint.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cell phone use during pregnancy and child behavioral problems in five birth cohorts

Abstract: Introduction Previous studies have reported associations between prenatal cell phone use and child behavioral problems, but findings have been inconsistent and based on retrospective assessment of cell phone use. This study aimed to assess this association in a multi-national analysis, using data from three cohorts with prospective data on prenatal cell phone use, together with previously published data from two cohorts with retrospectively collected cell phone use data. Methods We used individual participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
0
33
0
2
Order By: Relevance
“…Previous studies exploring the effect of lifestyle during pregnancy on the long-term health of children largely focused on the neurological and behavioral development. [29][30][31][32] A rodent model found that maternal lack of sleep in the third trimester can impair autonomic responses in male offspring with a long-term effect. 29 Cohort data among 83,884 mother-child pairs from ve countries revealed that maternal cellphone use during pregnancy increased the risk of hyperactivity in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exploring the effect of lifestyle during pregnancy on the long-term health of children largely focused on the neurological and behavioral development. [29][30][31][32] A rodent model found that maternal lack of sleep in the third trimester can impair autonomic responses in male offspring with a long-term effect. 29 Cohort data among 83,884 mother-child pairs from ve countries revealed that maternal cellphone use during pregnancy increased the risk of hyperactivity in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging human studies have begun to report that maternal exposure to MF nonionizing radiation during pregnancy is associated with an increased risk of several childhood illnesses, including immune-related conditions (such as asthma), 9 obesity, 10 and neurologic conditions (such as ADHD). 11,12 An experimental study 13 provided further evidence of (1) the direct link between in utero exposure to MF nonionizing radiation and ADHD in offspring and (2) a potential mechanism linking in utero exposure of MF nonionizing radiation with ADHD through altered neuronal developmental programming. Additional evidence from experimental animal studies has also recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…26 Cohorts data from 83,884 mother-child pairs from five countries revealed that maternal cellphone use during pregnancy increased the risk of hyperactivity in their offspring. 27 Another two prospective studies found that adequate physical activity during pregnancy could promote language development in children. 28,29 This study, for the first time, focused on maternal lifestyle choice and the susceptibility of childhood allergic disease.…”
Section: Discussionmentioning
confidence: 99%